Model kecerdasan emosi remaja Indonesia: Studi dengan penerapan Structural Equation Modeling: Emotional intelligence model of Indonesian adolescents: A study using Structural Equation Modeling - Dianti, Ine Luna; Soetjipto, Budi Eko; Chusniyah, Tutut; Farida, Ika Andrini (Persona:Jurnal Psikologi Indonesia, 2024)
Emotional intelligence is one of the predictors of adolescent success in the future, so the antecedents of emotional intelligence are very important to know. This study aims to examine the formation of adolescent emotional intelligence in terms of the influence of external factors, namely maternal authoritative parenting patterns, and internal factors, namely self-concept and emotional regulation. The research design used a quantitative approach on high school students (n = 377) of adolescent age who were selected by cluster random sampling. Adolescent emotional intelligence was measured using the TEI-Que Scale (α = 9.869), maternal authoritative parenting patterns were measured using the PSDQ Scale (α = 0.720), self-concept was measured using the PSC Scale (α = 0.928), and emotional regulation was calculated using the ERQ-Ca Scale (α = 0.892). The Structural Equation Model (SEM), which was processed through the AMOS version 26 program, was used to analyze the data. The research findings show that the mother's authoritative parenting pattern and self-concept mediated by emotional regulation have a positive and significant influence on the formation of adolescent emotional intelligence. The implications of this research are to provide support for Bandura's Social Cognitive Theory, which can be used as a reference in forming adolescent emotional intelligence.